PENGARUH KEPEMIMPINAN KEPALA SEKOLAH DAN MOTIVASI KERJA TERHADAP KINERJA GURU DI SD NEGERI KECAMATAN BOJA - Hindun; Noor Miyono (STKIP Subang, 2024)
The purpose of this study is to analyze the direc and indirect influence of principal leadership and work motivation on teacher performance. Education in schools cannot be separated from the role of teachers, where teachers in the world of education are very much needed in the teaching and learning process and distributing information that occurs in schools. Teachers are the most important human resources who are able to help students gain knowledge, insight and develop good personalities at school. Teachers have a big role and influence in realizing educational goals. However, the problem currently faced relating to the work motivation of elementary school teachers in Boja District is the low desire of teachers to learn IT, every time there are seminars or workshops related to increasing competency, not a few teachers only pay and entrust their names, apart from These teachers also copied previous tools in compiling administrative learning such as Syllabus, KI, KD, RPP, PROTA, and PROMES. This usually happens to create a mismatch with the conditions that exist in the field. This research is quantitative in nature using path analysis as data analysis using SPSS and Sobel. The sample for this research consisted of 46 teachers consisting of 12 elementary schools in Boja District, and was taken using Proportionated Cluster Random Sampling. The research instrument used a questionnaire. The results of the research show that the direct influence of the principal's leadership and work motivation has an influence on teacher performance. Meanwhile, the indirect influence of motivation is able to mediate the influence of the principal's leadership on teacher performance. In conclusion, there is an influence of the principal's leadership and work motivation on teacher performance.